Analisis Konsep Fisika Pada Kegiatan Larung Sesaji di Pantai Watu Ulo - Sakti Kalisa Sefanda; Ike Triwulandari; Efi Novitasari; I Ketut Mahardika; Singgih Baktiarso (Peneliti.net, 2023)
This observation aims to find out the methods that can be applied to science learning in the hope of advancing students' interest in studying cultural diversity based on science. The background of this observation comes from the cultural diversity and beliefs of the Indonesian people in terms of science. This diversity can be used as a source of physics learning that can be applied to students. One of them is the tradition of offering offerings in which there are principles of the application of physics. This observation was carried out in October-November 2022 at Watu Ulo Beach, Sumberejo Village, Ambulu District, Jember Regency, East Java. The method used in this observation is a qualitative analysis method. Namely, by obtaining data by technically analyzing data subjectively using interviews, observation, documentation and literature studies. Based on the results of observing the offerings, the concept of physics learning was obtained in the concept of pressure and sea waves. So, with this observation, it is hoped that students can understand the basic material of science in learning physics creatively, innovatively, effectively and efficiently.